Utilization of Processed Biofarmaka Plants as an Effort to Improve Household Economy in Sidokumpul Village, Bangilan District - Wulandari, Kartika; Kristiyoningsih, Kristiyoningsih; Fanani, Ahmad; Siswara, Hamzah Nata (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The primary aim of this community service program is to educate residents of Sidokumpul Village, Bangilan District, Tuban Regency, about the benefits of biofarmaka plants. The initiative addresses the underutilization of household yard space by encouraging the cultivation of biofarmaka, significantly enhancing community welfare through sustainable agricultural practices. Method: The study employs community education methods, including counseling, socialization, lectures, and discussions on biofarmaka utilization. Training sessions further facilitate technology diffusion, ensuring residents are well-informed about cultivation and processing techniques. Practical Applications: The research findings enable community members to effectively utilize their yard space, increasing household productivity and fostering self-reliance. This leads to improved economic conditions, as residents can produce processed products with higher added value, enhancing their household economy. Conclusion: The study concludes that the community understands the benefits of biofarmaka and has started cultivating them in their yards. Residents are also capable of creating higher-value processed products, contributing to a broader understanding of sustainable agriculture and improving household economies.